Treatment of relapsed multiple myeloma: Evidence-based recommendations. (January 2020) - Durer, Ceren; Durer, Seren; Lee, Sarah; Chakraborty, Rajshekhar; Malik, Mustafa Nadeem; Rafae, Abdul; Zar, Muhammad Abu; Kamal, Ahmad; Rosko, Nathaniel; Samaras, Christy; Valent, Jason; Chaulagain, Chakra; et al.
Abstract: The practice of choosing the next best therapy for patients with relapsed and/or refractory multiple myeloma (RRMM) is becoming increasingly complex. There is no clear consensus regarding the best treatment sequence for RRMM. With the approval of novel proteasome inhibitors (ixazomib and carfilzomib), immunomodulatory agents (pomalidomide), monoclonal antibodies (daratumumab and elotuzumab), and other targeted therapies, multiple combination regimens utilizing these agents are being studied with the goal of enhancing disease control, prolonging progression-free survival, and improving overall survival. We, herein, describe a review of FDA-approved regimens for RRMM patients and offer a paradigm in selecting subsequent treatment regimens, focusing on patient specific morbidity, treatment toxicity, and disease-specific characteristics.